(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth overview of the consonant sounds in the English language, focusing on their classification, articulation, and role in speech. It introduces the concept of phonemes, explaining how consonants are the building blocks of English words, and categorizes them based on three key articulatory features: place of articulation, manner of articulation, and voicing. The article further explores the different types of consonants, such as stops, fricatives, affricates, nasals, liquids, glides, and glottals, with examples to illustrate their pronunciation. It also discusses consonant clusters, which occur when multiple consonants appear together in syllables, adding complexity to English pronunciation. The conclusion emphasizes the importance of consonants in both the phonetic structure of English and its expressive potential. This resource is valuable for learners of English, linguists, and anyone interested in understanding the foundational sounds that shape the language.